2022
DOI: 10.1002/slct.202103602
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot Three‐component Solvent‐free Tandem Annulations for Synthesis of Tetrazolo[1,2‐a]pyrimidine and [1,2,4]triazolo[1,5‐a]pyrimidine

Abstract: β-Cyclodextrin, a robust organocatalyst has been explored for the straightforward and facile synthesis of tetrazolo[1,2a]pyrimidine and [1,2,4]triazolo[1,5-a]pyrimidine derivatives through one-pot three-component tandem annulations reaction under solvent-free condition using aldehyde, active methylene compound and 5-aminotetrazole or 3-amino-1,2,4-triazole respectively. This greener chemical procedure has advantages such as shorter reaction time, absence of toxic and hazardous catalyst, chemicals and solvent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The products are important in pharmaceuticals and natural product synthesis. 114 A study by Gein et al reported a one-pot reaction that was effective for the preparation of 7,7′-[2,2′-oxybis(ethane-2,1-diyl)bis(oxy)]bis(2,1-phenylene)]bis[5-methyl-N-(2-methylphenyl)-4,7-dihydrotetrazolo[1,5-a]pyrimidine-6-carboxamide (19) in 64% yield by annulation of 5-aminotetrazole (1), N-(2-methylphenyl)acetoacetamide (18), and formyl podand 17 at 170 °C (Scheme 21). 115 According to Filatova et al podands containing two terminal dihydrotetrazolo[1,5-а]pyrimidine groups 21 can be…”
Section: Scheme 17 Synthesis Of Dihydrotetrazolo[15-a]pyrimidinesmentioning
confidence: 99%
“…The products are important in pharmaceuticals and natural product synthesis. 114 A study by Gein et al reported a one-pot reaction that was effective for the preparation of 7,7′-[2,2′-oxybis(ethane-2,1-diyl)bis(oxy)]bis(2,1-phenylene)]bis[5-methyl-N-(2-methylphenyl)-4,7-dihydrotetrazolo[1,5-a]pyrimidine-6-carboxamide (19) in 64% yield by annulation of 5-aminotetrazole (1), N-(2-methylphenyl)acetoacetamide (18), and formyl podand 17 at 170 °C (Scheme 21). 115 According to Filatova et al podands containing two terminal dihydrotetrazolo[1,5-а]pyrimidine groups 21 can be…”
Section: Scheme 17 Synthesis Of Dihydrotetrazolo[15-a]pyrimidinesmentioning
confidence: 99%